Potencial antibacteriano e antioxidante de extratos aquosos das folhas da aroeira-do-sertão (Myracrodruon urundeuva Allemão) e sua aplicação como conservante natural em queijo frescal ultrafiltrado - Ferreira, Maria Jaiana Gomes (2021)
Myracrodruon urundeuva Allemão, popularly known as “aroeira-do-sertão”, is a medicinal plant that presents in its constitution several substances with bioactive properties, thus, potential for application in the food industry. In this context, the objective of this work was to evaluate the antibacterial and antioxidant potential of aqueous extracts of the leaves of aroeira-do-sertão (Myracrodruon urundeuva Allemão) and its application as a natural preservative in ultrafiltered fresh cheese. The extracts were obtained from fresh and dry cultivated Myracrodruon urundeuva leaves and four different extraction methods (decoction, infusion, maceration and turbolization). The identification of bioactive compounds and quantification of antioxidants, phenolic compounds, tannins and flavonoids in the extracts was performed and the antibacterial activity was tested on Gram-positive (Listeria monocytogenes and Staphylococcus aureus) and Gram-negative (Salmonella Enteritidis, Escherichia coli and Pseudomonas aeruginosa) evaluating the cell damage caused by the presence of extracts. In vitro toxicity and bioaccessibility were investigated by obtaining the percentage of bioactive compounds after gastrointestinal digestion. For the application tests, ultrafiltered fresh cheese with normal fat and light content, the extract obtained by maceration and Sthaphylococcus aureus was used. The aqueous extract obtained by decoction of aroeira-do-sertão leaves was effective against all tested microrganisms. The antimicrobial activity was verified for S. aureus and L. monocytogenes (0.2 and 0.8 mg/mL respectively) and for S. Enteritidis, P. aeruginosa and E. coli (6, 10 and 16 mg/mL respectively). Twenty-four secondary compounds distributed in six fractions were isolated. The fractions showed antimicrobial activity against Gram-positive bacteria at low concentrations (0.011 and 0.095 mg/mL) and two fractions showed activity against Gram-negative bacteria at higher concentrations (2.4 and 33 mg/mL). The Nuclear Magnetic Resonance analysis identified the presence of galotannis, gallic acid, flavonoids, proline derivative (N-Methyl-trans-4-hydroxy-L-proline) and quinic acid. The aqueous extracts of dry leaves obtained by decoction and maceration showed the best yields, antioxidant and antimicrobial potential. The bacterial structural damages caused by the extracts were roughness, cell wall loss, cell extravasation and change to L-shape. The UPLC-QTOF-MSE analysis of dry leaf extracts obtained by maceration and decoction identified thirteen compounds, predominantly flavonoids, tannins, gallic acid and quinic acid. After simulated gastrointestinal digestion, the significant presence of bioactive compounds with antioxidant potential was observed, demonstrating that these compounds can be accessible to the cells of the gastrointestinal tract and exert their health benefits in the body. The aqueous extract of the leaves obtained by maceration proved to be safe for application in cheese, not showing toxicity at the concentrations used in the experiments. The bioaccessibility of bioactive compounds in cheese added with the extract was quantified in the initial and final times. The extract showed potencial for use as an antibacterial against S. aureus in ultrafiltered fresh cheese with normal fat and light content, obtaining more efficiency in light cheese. Through microscopy it was possible to verify the presence of S. aureus inoculated in the cheese and the action of the extract on the plasma membrane. The presence of bioactive compounds from the extract added to ultrafiltered fresh cheese promoted antimicrobial and antioxidant action during storage.